Determinan Tax Avoidance pada Perusahaan Manufaktur: Peran Komisaris Pejabat/Mantan Pejabat, Leverage, Konsentrasi Pelanggan, dan Kepemilikan Institusional - Andre Nugroho; Desta Dwi Ramadhan; Riska Lailatul Fitri; Aisha Salsabila; Muhammad Islam Izzatii; Arif Nugrahanto (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study examines the effects of politically connected commissioners (current or former government officials), leverage, customer concentration, and institutional ownership on tax avoidance among manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Using a quantitative approach with Panel-Corrected Standard Errors (PCSE) and purposive sampling, the final sample comprises 56 firms (280 firm-year observations). The findings indicate that leverage significantly increases tax avoidance, and the presence of commissioners who are current or former government officials further amplifies firms’ propensity to engage in tax avoidance. In contrast, institutional ownership significantly promotes tax compliance, while customer concentration has no significant effect on tax avoidance. Therefore, tax supervision and governance should be prioritized for firms with high leverage and strong political connections, as they are more prone to engage in tax avoidance.